Safe Discharge Home With Telemedicine of Patients Requiring Nasal Oxygen Therapy After COVID-19 - Dinh, Aurélien; Mercier, Jean-Christophe; Jaulmes, Luc; Artigou, Jean-Yves; Juillière, Yves; Yordanov, Youri; Jourdain, Patrick; , The AP-HP/Universities/INSERM COVID-19 Research Collaboration; Aurélien, Dinh; Jean-Christophe, Mercier; Jean-Yves, Artigou; Yves, Juillière; et al. (Frontiers in Medicine, 2021)
Introduction The COVID-19 pandemic created challenges to healthcare systems worldwide. During the pandemic, patients with COVID-19 from greater Paris area were monitored at home using a web-based remote system called COVIDOM™, using self-administered questionnaires, which triggered alerts to a regional control center. Patients still requiring low-flow oxygen therapy discharged home were also included in this telemedicine solution. We aim to evaluate the safety of this original management. Methods We conducted a retrospective multicenter cohort of patients monitored by questionnaire and trained physicians using COVIDOM. During late follow-up, the status of the patients using a Euro-Qol (EQ-5D-5L) questionnaire, and the Medical Research Council (MRC) Dyspnea scale was collected. Results From March 21st to June 21st 2020, 73 COVID-19 patients still receiving nasal oxygen at hospital discharge were included. Median [Inter-Quartile Range (IQR)] age was 62.0 [52.5-69.0] years, 64.4% were male. Altogether, risk factors were observed in 49/73 (67%) patients, mainly hypertension (35.6%), diabetes mellitus (15.1%) and active neoplasia (11.0%). Among the cohort, 26% of patients were previously managed in ICU. Oxygen therapy was required for a median [IQR] of 20 [16-31] days. No death or urgent unplanned hospitalization were observed during the COVIDOM telemonitoring. During late follow-up evaluation, the mean EQ-5D-5L questionnaire score was 7.0 ± 1.6, and the mean MRC dyspnea scale was 0.8 ± 1.0, indicating absence of dyspnea. Five patients have died from non-COVID causes. Conclusions In this preliminary study, early discharge home of patients with severe COVID-19 disease who still required low-oxygen therapy seems to be safe.